Relationship between employees’ work outcomes and work – family enrichment among workers in government sector - Rahimah, Hamid; Dayang Kartini, Abang Ibrahim (-, 2012)
This study aims to investigate the relationship between employees’ work outcomes and work-family enrichment among workers in government sector. The researcher focus on positive work outcomes such as job satisfaction, job commitment and job performance. A quantitative survey approach by using questionnaires had been carried out as instrument for data collection. 250 sets of questionnaires were distributed to the both women and men workers at Bangunan Sultan Iskandar, Simpang 3, Kuching, Sarawak. However, only 122 sets of valid questionnaires were being returned and used for the analysis. Pearson Correlation “r” had been used to identify the relationship between job satisfaction, job commitment and job performance with work – family enrichment. The findings revealed that there are significant relationship between job satisfaction, job commitment and job performance with work – family enrichment. Thus, it is recommended that the organization should enhance to their workers on awareness of work and family balance is necessary for ensuring that employees will able to handle life and work properly that will contribute to good work. Furthermore, family development practitioners should work together with HR practitioners in designing program to help women and men, cope with the demand of work and family roles.